1988
DOI: 10.2307/1541897
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Osmoregulation and Salinity Tolerance in Two Decapod Crustaceans:Homarus americanusandPenaeus japonicus

Abstract: Osmoregulation and salinity tolerance were studied in larvae and post-larvae of two species of crustaceans. Homarus americanus and Penaeus japonicus, that have different types of embryonic development.In both species, salinity tolerance decreased through the larval stages, was at a minimum at metamorphosis, and increased in post-larval stages. In H. americanus, the lethal salinity for 50% of the animals (24 h LS50) at 20C was about 1 7%o at metamorphosis, and about 10.5-12%o in stages IV and V. In P. japonicus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
2
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 28 publications
5
63
2
2
Order By: Relevance
“…Among the intrinsic factors, the ontogeny of osmoregulation, especially, needs further investigation, i.e. the development of regulatory structures (Hong, 1988;Bouaricha et al, 1994) and endocrine systems (Charmantier et al, 1988;Bouaricha et al, 1991;Charmantier and Charmantier-Daures, 1991). In our study, larval respiration was in general reduced at low salinities.…”
Section: Discussionmentioning
confidence: 51%
“…Among the intrinsic factors, the ontogeny of osmoregulation, especially, needs further investigation, i.e. the development of regulatory structures (Hong, 1988;Bouaricha et al, 1994) and endocrine systems (Charmantier et al, 1988;Bouaricha et al, 1991;Charmantier and Charmantier-Daures, 1991). In our study, larval respiration was in general reduced at low salinities.…”
Section: Discussionmentioning
confidence: 51%
“…They reported better survival of juveniles in salinities of 2 ppt and 0 ppt, compared to postlarvae. Other studies in L. vannamei 20 , and other penaeid species such as M. japonicus 4 , P. indicus 10 and L. setiferus 18 have also shown that salinity tolerance increases with PL age. Increased survival seen at the juvenile stages suggests that by this stage L. vannamei develops increased osmoregulatory capacity as has been reported for other decapod crustaceans 4 .…”
Section: Discussionmentioning
confidence: 81%
“…Other studies in L. vannamei 20 , and other penaeid species such as M. japonicus 4 , P. indicus 10 and L. setiferus 18 have also shown that salinity tolerance increases with PL age. Increased survival seen at the juvenile stages suggests that by this stage L. vannamei develops increased osmoregulatory capacity as has been reported for other decapod crustaceans 4 . PL size has been indicated to be indirectly correlated to a larger gill area, which in turn is thought to represent a better osmoregulatory capacity 1 .…”
Section: Discussionmentioning
confidence: 81%
“…This ontogenic change in the patterns of osmoregulation can be compared with that in other species, and it may be assigned to one of 3 different types that have been proposed (Charmantier et al 1988;review in Charmantier 1998). Armases miersii belongs to the third category, in which the pattern of osmoregulation changes during the postembryonic development.…”
Section: Medium (Psu)mentioning
confidence: 97%
“…The latter occurs in species where metamorphosis is spread over several molts, e.g. in Penaeus japonicus and probably other penaeid shrimps (Charmantier et al 1988). In the literature, there are controversial views of the timing of metamorphosis in brachyurans.…”
Section: Medium (Psu)mentioning
confidence: 99%